A new species of the genus Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from the northern part of Kamchatka kray - Ryabukhin, A.S. (Zenodo, 2018)
Ryabukhin, A.S. (2018): A new species of the genus Lathrobium Gravenhorst, 1802 (Coleoptera: Staphylinidae, Paederinae) from the northern part of Kamchatka kray. Far Eastern Entomologist 354: 15-18, DOI:10.25221/fee.354.2, URL: http://dx.doi.org/10.25221/fee.354.2